(untitled) (Bangladesh Journal of Agricultural Research, 2012)
The experiment was carried out at the Germplasm Centre of Bangladesh Agricultural University, Mymensingh during the fruiting season of 2005-06 to investigate the effects of fertilizer and its installment of application on harvesting time, yield and quality of fruits of 8 years old mango plant cv. Amrapali. Four fertilizer doses i.e. T1 : 50% of the fertilizer dose (cowdung 12.5 kg, urea 375 g, TSP200g, MoP125 g, gypsum 125 g and zinc sulphate 7.5 g per plant), T2 : 100% of the fertilizer dose (cowdung 25 kg, urea 750 g, TSP400 g, MoP 250 g, gypsum 250 g and zinc sulphate 15 g per plant), T3 : 150% of the fertilizer dose (cowdung 37.5 kg, urea 1125 g, TSP 600 g, MoP 375 g, gypsum 375 g and zinc sulphate 22.5 g per plant), and T4 : control (no fertilizer) and three splits of application i.e. A1 : One installment (whole fertilizer applied on 15 September), A2 : Two installments (15 September and 15 March) and A3 : Three installments (15 September, 15 March and 15 May) were included as treatments. Plants receiving 150% of the fertilizer dose in three installments caused delayed harvest by 11 days compared to control than that of the control. Plants treated with 150% of fertilizer dose in combination with three installments produced the highest number of fruits (96/ plant) as well as the highest yield (19.55 kg/plant) as compared to control (23/ plant and 3.48 kg/plant). Applying fertilizer at 150% of the fertilizer dose in three installments improved the fruit quality with regard to TSS, pH, titratable acidity, vitamin C, moisture content, dry matter content, reducing sugar, non reducing sugar and total sugar content over control. Thus, this treatment may be recommended for fertilizer management in mango cultivation. DOI: http://dx.doi.org/10.3329/bjar.v37i2.11231 Bangladesh J. Agril. Res. 37(2): 279-293, June 2012